Esophagus-to-posterior Atrial wall relationship: pre- and Intra-procedural three-dimensional multimodality imaging for esophageal position. (24th May 2021) - Teres, C; Soto-Iglesias, D; Penela, D; Jauregui, B; Chauca, A; Ordonez, A; Carreno-Lineros, JM; Scherer, C; Huguet, M; Ramirez-Paesano, C; Oller, G; Panaro, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Dr Teres was funded by the research fellowship grant of the Swiss Heart Rhythm Foundation. Dr Carreno-Lineros was funded by a Scholarship from Sociedad Española de Cardiología (SEC). Introduction:   pulmonary vein isolation (PVI) approach implies unavoidable ablation  on the posterior atrial wall which is closely related to the esophagus. PVI may result in several complications. Objective: the present study aims to analyze the stability of the esophageal position inside the mediastinum at the level of the posterior atrial wall from one procedure to another (Redo group) and during a single procedure (multi-image group). Methods: the esophageal position was compared in two groups. First, pre-procedural multidetector computerized tomography (MDCTs) of the first PVI and the redo intervention (Redo group) were segmented with ADAS 3D™ software to compare the esophageal position and the atrio-esophageal distance prints (Figure A). Second, three imaging modalities were compared for the same procedure (multi-image group): i) preprocedural MDCT; ii) intraprocedural fluoroscopy obtained with the TEE probe in place in three projections with CARTOUNIVU™ (Biosense Webster); and iii) esophageal fast-anatomical map (FAM) obtained at the end of the procedure (Figure D). Ablation procedures were performed under general anesthesia. Exclusion criteria were unavailability or contraindication to obtain any of the techniques. The 3D correlation of the esophageal position acquired with different techniques, was computed in Matlab using semiautomatic segmentation analysis. Results: 35 patients were analyzed for the Redo group. Mean age 61 ± 10 years, 17 (65%) male, mean LVEF 57 ± 7%, mean LA diameter 43 ± 5 mm, median time since previous ablation (and therefore between MDCT acquisitions) was 6 months (IQR 3-9). Mean atrio-esophageal distance for both MDCTs was 1.2 ± 0.6 mm . The esophageal trajectory as related to the atrial posterior wall was left for 20 (57%) patients, central for 6 (18%) patients, and right for 3 (9%) patients, left-central for 4 (11%) patients, and right-central for 2 (5%) patients. There was a 91 ± 5% correlation on the esophageal position between the first procedure and the redo procedure MDCT. In 3 cases the position was clearly different with a correlation of only 40 ± 22%. The multi-imaging group was composed of 100 patients, mean age 61 ± 10 years, 17 (65%) male, mean LVEF 56 ± 7%, mean LA diameter 39 ± 6 mm. The esophageal trajectory as related to the atrial posterior wall was left for 55 (55%) patients, central for 23 (23%) patients, and right for 9 (9%) patients, left-central for 8 (8%) patients, and right-central for 5 (5%) patients. The correlation between MDCT and CARTOUNIVU™ was 82 ± 10% (Figure B); between MDCT and ESOFAM 80 ± 12% (Figure B); and between ESOFAM and CARTOUNIVU™ 83 ± 15% (Figure C). Conclusions: There is a high stability of the esophageal position between procedures and from the beginning to the end of procedure. This observation needs to be tested for its clinical utility by designing studies that take into account the esophagus distance print to modulate RF delivery